Cystadenocarcinoma of the gallbladder: A case report. (December 2022) - Hammami, Y.; Sebai, A.; Ouadi, Y.; Ben Mahmoud, A.; Frikha, W.; Bel Hadj Ali, J.; Fteriche, S.; Kacem, J.M.
Abstract: Introduction and importance: Cystadenoma and cystadenocarcinoma of the biliary duct remain a rare diagnosis, the localization is intrahepatic in 97% of the cases and extrahepatic in 3%of them [1]. Cystadenocarcinoma of the gallbladder is the rarest localization, it's usually diagnosed late because of the poor symptoms and the nonspecific lesions in the different imaging. Only hundreds of cases have been reported for cystadenocarcinoma of the gallbladder. This case report has been reported in line with the SCARE Criteria. Case presentation: We present a 70-year-old woman, with no family or personal history, who was complaining of pain in the right hypochondrium and an altered general well-being, with no other clinical abnormalities. The imaging including abdominal sonography, CT scan, and MRI concluded at a budding lesion formed in the gallbladder wall which measured 65 × 15mm. Cancer of the gallbladder was suspected and the patient was operated. A resection of segment s4b and 5 of the liver was performed with lymphadenectomy. The post-operative clinical course was uneventful. The diagnosis of cystadenocarcinoma of the gallbladder was confirmed on an anatomopathological exam of the specimen. Conclusion: Cystadenocarcinoma is a rare diagnosis. There are no specific symptoms or lesions at the imaging. The confirmation is obtained on an anatomopathological study of the specimen. Highlights: Cystadenocarcinoma is a rare diagnosis. There are no specific symptoms nor lesions at the imaging. The confirmation is done on an anatomopathological study on the specimen.